PENGEMBANGAN E-MODUL BERBASIS INKUIRI TERBIMBING TERINTEGRASI NILAI-NILAI KARAKTER PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS XI - Eva Oktaviana; Triana Asih; Handoko Santoso (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
This development research aims to produce teaching material products in the form of guided..inquiry-based e-modules integrated with character values ​​in human digestive system materials that are suitable for use. The development of this e-module uses a 4-D model, covering four stages, namely, Define (analyze needs), Design (design e-module products), Develop (develop designed e-module products), and Disseminate (Product deployment). The instrument used is an assessment questionnaire. There are two types of questionnaires used, namely the first expert validation questionnaire with 2 assessments (material and design). Both student response questionnaires. The e-module is validated by design and material experts, both validators provide suggestions and comments to improve the e-module. Products that have been revised on the advice of design experts get an average percentage score of 95% and material experts get an average..percentage score of 91%. The e-module product was tested in Class XI IPA SMA Muhammadiyah 2 Metro. Getting a score of all aspects getting a percentage of 89%. The results of expert validation and student responses show that the e-module developed is